Synthesis of TiO2-SiO2 powder photocatalyst via sol-gel method: effect of titanium precursor type on powder properties - Abd Aziz, Radhiyah; -, Nor Asyikin; Iis, Sopyan (The Instituition of Engineers Malaysia, 2009)
TiO2 -SiO2 powder photocatalysts with varied SiO2 portion were prepared through sol-gel technique using two types of metal alkoxides: titanium tetraisopropoxide (TPT) and titanium diisopropoxide (PTP). Tetraethoxysilane (TEOS) as the silicon precursor was partially hydrolysed at room temperature, followed by the dropwise addition of these two metal alkoxides to produce polytitanosiloxane (PTS) solution. Hexane filtration of the PTS solution followed by drying and calcination gave TiO2 -SiO2 powder. The physico-chemical characteristics of the obtained powders were investigated using TG-DTA, FTIR, XRD, and FESEM. Both types of powder particles were in nano-sized with spherical shape. The powder derived from PTP showed particle size smaller than that derived from TPT. From TGA analysis, it can be observed that the PTP derived powder start to crystallise at lower temperature compared to the TPT derived powder. However, TPT derived powder showed a stability of anatase crystal structure even after high temperature calcination